1996
DOI: 10.1021/jo960017t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantiopure syn-β-Amino Alcohols. A Simple Case of Chelation-Controlled Additions of Diethylzinc to α-(Dibenzylamino) Aldehydes

Abstract: Enantiomerically pure syn-2-amino alcohols 6 are prepared by addition of diethylzinc to chiral alpha-(dibenzylamino) aldehydes 4. The addition is highly stereoselective, leading to syn-2-(dibenzylamino) alcohols 5 with excellent diastereomeric excesses (76-98%). Debenzylation of 5 by hydrogenolysis on Pearlman's catalyst yields quantitatively the amino alcohols 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…To investigate the effect of the stereochemistry of the Schiff base ligands on the enantioselectivity of the product, we also prewww.eurjoc.orgpared ligand 4 (Scheme 1), a diastereomer of ligand 3i, according to a literature method. [27] Under the same reaction conditions, ligand 4 afforded the product in moderate yield but with poor enantioselectivity ( The result indicated that syn diastereomer 3i (S,R) exerted a stronger chiral discrimination effect than anti diastereomer 4 (S,S) in the reaction. The solvent effect of the VO(acac) 2 /3i system was examined.…”
Section: Resultsmentioning
confidence: 93%
“…To investigate the effect of the stereochemistry of the Schiff base ligands on the enantioselectivity of the product, we also prewww.eurjoc.orgpared ligand 4 (Scheme 1), a diastereomer of ligand 3i, according to a literature method. [27] Under the same reaction conditions, ligand 4 afforded the product in moderate yield but with poor enantioselectivity ( The result indicated that syn diastereomer 3i (S,R) exerted a stronger chiral discrimination effect than anti diastereomer 4 (S,S) in the reaction. The solvent effect of the VO(acac) 2 /3i system was examined.…”
Section: Resultsmentioning
confidence: 93%
“…[15] We were interested in the use of Ruppert's reagent (TMSCF 3 ) as a trifluoromethylation agent because of the mild reaction conditions that promote the addition. Thus, the reaction of homochiral dibenzylamino aldehydes 1aϪf [16] with an excess (1.5 equiv.) of TMSCF 3 and a catalytic amount of TBAF (0.05 equiv.)…”
mentioning
confidence: 99%
“…Starting α-(dibenzylamino) aldehydes 1a-c were prepared as described previously. [10] The 1 H (300 MHz) and 13 C NMR (75 MHz) spectra were recorded on a Bruker AC 300 or AMX 300 spectrometer using TMS as the internal standard. IR spectra were recorded on a Perkin-Elmer Spectrum BX spectrometer as a film or KBr dispersion.…”
Section: Methodsmentioning
confidence: 99%
“…The 2-and 2,6-substituted 3-hydroxypiperidines were synthesized starting from α-dibenzylamino aldehydes 1a-c readily prepared [10] from commercially available α-amino acids. These aldehydes reacted with 4-butenylmagnesium bromide in diethyl ether at 0°C to afford the Felkin-Anh anti-2a-c amino alcohols in good yields and with excellent diastereoselectivities (Scheme 2 and Table 1).…”
Section: Introductionmentioning
confidence: 99%